Effect of Treatment Age on Mechanical Properties of Geopolymer Concrete - Diana Ningrum; Handika Setya Wijaya; Elisabeth Van (Asian Journal Science and Engineering, 2022)
There are the same compound content, fly ash does not have the ability to bind, so it requires an alkaline activator for the polymerization reaction or binding reaction to occur. The alkali activators commonly used are sodium hydroxide and sodium silicate. The use of these materials makes concrete with fly ash known as geopolymer concrete. Geopolymer concrete is an alternative to conventional concrete, so it must have optimal strength like conventional concrete, therefore researchers are interested in testing the value of compressive strength, split tensile strength and mode of elasticity of geopolymer concrete using 10 molar alkali activator with a ratio of 3:2. for variations in the age of concrete 7, 14, 21, and 28 days; and the conversion value of geopolymer concrete using 10 molar alkali activator with a ratio of 3:2 for variations in the age of concrete 7, 14, 21, and 28 days. This research is an experimental study using variations in the age of concrete 7, 14, 21, and 28 days for geopolymer concrete using 10 molar alkali activator with a ratio of 3:2. The results of this study indicate that there is an effect of variations in the age of concrete on the value of compressive strength, split tensile strength, and modulus of elasticity of geopolymer concrete. Where the compressive strength, split tensile strength, and modulus of elasticity of geopolymer concrete at the age of 7 days are 31.40%; 35.44%; and 23.32% which at the age variation of 28 days increased by 100%. In addition, in this study, it is known that the conversion value at the age of 28 days for variations in the age of 7 days, 14 days, 21 days, and 28 days, respectively, is 0.31; 0.73; 0.97; 1.00 Keywords: Geopolymer Concrete, Compressive Strength, Modulus of Elasticity